PROFESIONALISME GURU DAN TANTANGANYA DI ERA KURIKULUM DEEP LEARNING: PROFESIONALISME GURU DAN TANTANGANYA DI ERA KURIKULUM DEEP LEARNING - Faizin, Faizin; Egar, Ngasbun; Wuryandini, Endang (JURNAL ILMIAH EDUNOMIKA, 2025)
This study analyzes partially and simultaneously the influence of principal leadership, work culture, and motivation on the professionalism of junior high school teachers in sub-rayon 01 Grobogan Regency in the Deep Learning Curriculum Era. This study uses a quantitative approach with an explanatory research type. The study population was 292 teachers, with a sample of 166 teachers selected using proportional random sampling techniques. Data were collected through questionnaires and analyzed using descriptive statistics and multiple linear regression. The results showed that respondents' perceptions of principal leadership and work culture were in the good category, while perceptions of work motivation and teacher professionalism were in the very good category. Hypothesis testing showed that principal leadership, work culture, and work motivation partially influenced teacher professionalism. Principal leadership was strongly correlated and contributed 60.7%. Work culture was strongly correlated and contributed 61.4%. Motivation was very strongly correlated and contributed 73.2% to teacher professionalism. Together, principal leadership, work culture, and work motivation were very strongly correlated and contributed 82.5% to teacher professionalism. In conclusion, optimizing teacher professionalism in the deep learning curriculum era requires a holistic and integrated approach. Transformational, communicative and appropriate leadership of the principal in making decisions, a work culture that includes behavioral values, norms and organizational climate, and high internal and external motivation of teachers are important factors that are interrelated and influence teacher professionalism. By paying attention to these three aspects, it is hoped that the quality of teachers and education in Indonesia can continue to improve.